The Implementation of Video in Teaching Writing Procedure Text to the Tenth Grade Students at SMK Wijaya Sukodono - Mochammad Miftakhul Afandi (P-SEMART JOURNAL, 2021)
Writing is one of the abilities that is very important for students, because by writing students can convey the contents of their minds in written form, and by using video as a medium. Students find it easier to express their ideas. This research is focused to describe the application of using video media in writing procedure texts and to describe the responses of students writing procedure texts using video media. This research is a descriptive qualitative research. The tenth grade of SMK Wijaya Sukodono is the subject of this study. The data in this study are checklist and questionnaire data and documentation during the learning process. All activities during the procedure text learning using video media are the source of data in this study. The results showed that learning to write tech procedures using video media can be done in the tenth grade of Wijaya Sukodono. In addition, student responses to the use of video media have many positive impacts for students, reinforced by the results of the questionnaire which showed 73% of students gave positive responses and 27% of students gave negative responses. Based on the results, the researcher found that video as a media could be applied in teaching writing very well especially teaching writing procedure texts. The researcher concludes that the video is suitable to be applied in teaching writing procedure texts for tenth grade students of SMK Wijaya Sukodono.